USAHA TANI HORTIKULTURA DI KABUPATEN POSO: SEBUAH KOMPARASI PENDAPATAN USAHA TANI BAWANG MERAH DAN KUBIS - Feliks Arfid Guampe; Join Hengkeng; Novi Maryam Lempao; Yames Sido (University of Jember, 2022)
The farming sector is an important part of Indonesia’s national development due to its availability of foodstuffs, industrial resources, bio-energy, labor absorption, and income source for the rural populace. The horticultural practices, such as farming vegetables, fruits, medicinal herbs and ornamental plants, are strategic subsectors in the progression of the national and regional farming industry. This study aims to determine the performance of farming and to compare the income of horticultural farming of cabbage and shallots in the Poso Regency. A combined method is utilized in this research. Qualitative data analysis will descriptively portray the production and processing stages, cost, market access, and farmers’ income, while quantitative analysis will calculate the profit and Return-Cost Ratio. The research shows that farmers’ revenue depends on the size of land they possess. After a planting season, the net income of shallot farmers is between Rp 116.045.237 and Rp139.647.762, whereas cabbage farmers earn a total net income between Rp 18.131.412 and Rp 83.141.875. This demonstrates that horticultural farming, namely shallot cultivation, is more profitable than cabbage.